Kajian Kriminologis tentang Kecenderungan Pelaku dalam Melakukan Kejahatan Berat yang Mengakibatkan Matinya Korban di Kota Kupang - Ga, Jurondly Marcky Iverson; Manafe, Deddy R Ch; Dima, Adrianus Djara (Law Faculty, Nusa Cendana University, 2025)
This study examines the tendency of perpetrators to commit serious crimes that result in the death of victims in Kupang City, with the main focus on the crime of murder. Based on these problems, this study focuses on two main aspects, namely: (1) factors that cause someone to tend to commit the crime of murder, and (2) the role of the social environment and the legal system in influencing this tendency. This study uses an empirical research method with a qualitative approach. Data were obtained through documentation studies of court decisions, interviews with perpetrators of crimes at the Kupang Class IIA Penitentiary, and analysis of the factors causing the crime. The results of the study indicate that the tendency of someone to commit the crime of murder is influenced by various factors, including emotional drives, revenge, the influence of alcohol, and social and economic conditions. In addition, weak social control and a less supportive environment also contribute to the increased risk of someone committing serious crimes. Therefore, more effective prevention efforts are needed through social and legal approaches, including increasing legal education in the community, monitoring the factors that trigger crime, and strengthening the role of law enforcement officers in handling murder cases more optimally.